Management Audit to Assess the Effectiveness of Sales Management at PT. XX - Syah, Syafrial (PT Inovasi Pratama Internasional, 2024)
Background: Companies use marketing management audits to evaluate the effectiveness of their marketing function and determine competitive strategies to maintain their survival. Objective: This report presents a management audit of the marketing function at PT. The aim of this study is to assess the efficacy of the marketing function implementation and identify areas for improvement, in order to provide suggestions and recommendations. The research methodology involves a descriptive qualitative approach using a case study method, which includes observation, documentation, interviews, and questionnaires. The assessment was based on a comparison of criteria, causes, and effects. According to the research conducted, it can be inferred that the implementation of the marketing function has not been as effective as desired. According to the research conducted, it can be inferred that the implementation of the marketing function has not been as effective as desired. According to the research conducted, it can be inferred that the implementation of the marketing function has not been as effective as desired. It was found that there are several internal and external factors that could be considered weaknesses for the company.